Raymond Williams: Politics, Education, Letters - Morgan, W John. author. aut Link
X, 215 p.
Keywords: The specially commissioned essays collected in this volume reflect the full range of Raymond Williams's interests and concentrate not only on the exposition and evaluation of his ideas, but also on how they have influenced teachers, writers, and other thinkers.